2016
DOI: 10.1016/j.joa.2016.10.561
|View full text |Cite
|
Sign up to set email alerts
|

Epicardially placed implantable cardioverter‐defibrillator for a child with congenital long QT syndrome

Abstract: A 7-year-old boy presented at our hospital with syncope. At birth, electrocardiography had shown a long QT interval with torsade de pointes (TdP). Congenital long QT syndrome (LQTS) had been diagnosed by genetic testing, and was successfully controlled with oral propranolol. At age 7, TdP had recurred with syncope. Electrocardiography revealed a prominent long QT interval with T-wave alternans. The propranolol dose was increased, but TdP remained uncontrolled. A cardioverter-defibrillator (ICD) was implanted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This procedure was previously performed in a 7-year-old patient with long QT syndrome type 2 in our hospital. 8 …”
Section: Discussionmentioning
confidence: 99%
“…This procedure was previously performed in a 7-year-old patient with long QT syndrome type 2 in our hospital. 8 …”
Section: Discussionmentioning
confidence: 99%
“…As previously described, pericardial placement of a defibrillation coil provides a safe and efficacious approach to ICD therapy in young children when a transvenous system is not feasible [3] , [4] . The configuration of a posteriorly and superiorly placed coil in the oblique sinus and abdominal generator demonstrates low and stable defibrillator energy and stable impedance.…”
Section: Case Reportmentioning
confidence: 91%
“…The effect of beta-blockade on quantitative microvolt TWA has not previously been investigated in LQTS patients, although a few cases of reduction or elimination of macroscopic TWA by betablockade and improvement in symptoms in pediatric LQTS patients have been reported (Bosi et al, 2002;Mache et al, 1996;Sugiyama et al, 2017). Japanese Circulation Society guidelines recommend microvolt TWA for prediction of sudden cardiac death in patients with ischemic (JCS Joint Working Group, 2012; Klingenheben, Grönefeld, Li, & Hohnloser, 2001;Rashba et al, 2002) or non-ischemic cardiomyopathy (JCS Joint Working Group, 2012; Klingenheben et al, 2001); in these populations, metoprolol (Klingenheben et al, 2001), d,l-sotalol (Klingenheben et al, 2001, and esmolol (Rashba et al, 2002) have been reported to suppress microvolt TWA along with arrhythmia (Verrier & Ikeda, 2013).…”
Section: Twa and Arrhythmia Risk In Lqts Patientsmentioning
confidence: 99%
“…Although a few case reports demonstrated that beta-blockade reduces "macroscopic" TWA in association with arrhythmias in LQTS (Bosi, Cappato, Priori, & Stramba-Badiale, 2002;Mache et al, 1996;Sugiyama et al, 2017), the effect of beta-blockade on microvolt levels of TWA in LQTS patients has not been systemically investigated.…”
mentioning
confidence: 99%